Control of western corn rootworm damage by application of soil insecticides at different maize planting times. (March 2017) - Blandino, Massimo; Ferracini, Chiara; Rigamonti, Ivo; Testa, Giulio; Saladini, Matteo A.; Jucker, Costanza; Agosti, Mauro; Alma, Alberto; Reyneri, Amedeo
Abstract: The western corn rootworm, Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae) (WCR), is one of the most damaging maize crop pests. Damage to maize is primarily caused by the larvae feeding on roots, which results in a reduction of water and nutrient uptake and may cause lodging as well as a substantial reduction in grain yield. The effects of soil insecticides, applied at different planting times, on controlling WCR damage were investigated in 76 naturally infested fields in Northern Italy over a 4-year period. Without furrow insecticides, plant density was reduced at all of the considered planting times (−5%). Insecticide application led to a significant reduction in the WCR larval density (−43%). As a consequence, the root injury measured by node injury scale, was reduced (−65%) as was the incidence of plants with "gooseneck" symptoms (−76%). Furthermore, the soil-applied insecticide plots showed a significant increase in plant biomass yield at the dough stage (+6%) and in grain yield at physiological maturity (+8%). The application of soil insecticides showed a positive yield increase in 95% of the compared production situations. The yield increase was higher than 5% in 70% of considered cases. The effect of the soil-applied insecticides on root and plant damage symptoms, and the consequent biomass and grain advantage were steady over the different intervals between planting time and WCR egg hatching. The results of this study have underlined that the application of a soil insecticide to the furrows at planting leads to a clear control of injuries from insects and a consequent maize yield advantage. Graphical abstract: Highlights: The role of soil insecticides on controlling WCR was investigated in 76 maize fields. Soil insecticides applied at planting clearly controlled WCR root injuries. WCR control through soil-applied insecticides leads to clear biomass and grain increase. The effect of soil-applied insecticides were steady among the different planting times.